Aplicación de la guía del PMBOK® para la planificación de la reconstrucción y rehabilitación del aeropuerto internacional Eloy Alfaro de la ciudad de Manta - Herrera Proaño, Renato Gabriel (2019)
This work was developed in order to provide the planification for reconstruction and rehabilitation of Eloy Alfaro International Airport, in the city of Manta. To achieve this goal, standard practices provided by the PMBOK® Guidelines were used to develop in an orderly and structured manner all the knowledge areas required to identify the most likely behavior and to accomplish the project goals related to the triple restriction proposed in costs, time and reach. The most relevant data include the identification of the risks that might be encountered in this project and how they can be solved. Hence, mitigation actions to negative effects that may be recognized along the duration of the project are proposed. The financial analysis of the project was diagnosed within the framework of expert judgements and historic data of past projects. The analysis of this data allows to get a close approach to the project viability. To contemplate this viability, the net present value and the internal rate of return were taken as indicators, also 100 percent of the affectation of the negative risks of the management margin was considered and the reserve controlled by the company in charge of the planning and reconstruction of the Airport.